Evaluating the rate of reversal of fentanyl-induced respiratory depression using a novel long-acting naloxone nanoparticle, cNLX-NP - Averick, Saadyah E.; Kassick, Andrew J.; Song, Daihyun; Zhang, Borui; Vigliaturo, Jennifer; Luengas, Diego; Silva-Ortiz, Pedro; Pravetoni, Marco; Raleigh, Michael D. (Frontiers in Psychiatry, 2024)
Fentanyl and fentanyl analogs (F/FA) have become increasingly common adulterants in counterfeit prescription pills and illicit street drug mixtures due to their ease of synthesis and exceedingly high potency. The ongoing epidemic of fatal overdoses fueled by F/FA continues to highlight the need for longer-acting therapies than naloxone (NLX), the current gold-standard for reversing opioid overdoses, which shows limited efficacy to prevent renarcotization associated with F/FA toxicity. A novel opioid reversal agent based on covalent naloxone nanoparticles (cNLX-NP) has been shown to blunt fentanyl-induced respiratory depression out to 48 hr, demonstrating its potential therapeutic utility. The purpose of this study was to characterize how rapidly cNLX-NP reverses fentanyl-induced respiratory effects as well as the duration of its protective effects.Sprague Dawley male rats (n=6/group) were tested on an oximeter for baseline percent arterial oxygen saturation (%SaO2) challenged with 0.1 mg/kg SC fentanyl and 15 min later given 10 mg/kg IM doses of NLX, nalmefene (NLMF), or cNLX-NP and continuously monitored via oximetry for 10 minutes. One week later the experiment was repeated using a 1:1 mixture of NLX:cNLX-NP as the reversal agent in the rats that previously received NLX alone. While both NLX and NLMF rapidly reversed %SaO2 to baseline within 1 min, rats that received cNLX-NP did not return to >90% SaO2 levels until 9 min after administration. Similarly, heart and breath rates returned to baseline within 1 min of treatment with NLX and NLMF but did not return to baseline until 10 minutes after cNLX-NP administration. In contrast, NLX:cNLX-NP reversed all fentanyl-induced respiratory depressive effects within one minute. While cNLX-NP alone may not sufficiently reverse F/FA overdose in a timely manner, mixing free NLX with cNLX-NP can provide a mechanism to both rapidly reverse fentanyl-related effects and maintain extended protection against synthetic opioid toxicity. These data support further development of cNLX-NP as a fastacting and long-lasting antidote to treat F/FA-induced respiratory depression and overdose, and potentially prevent renarcotization in humans.